Expression of CD38 in Mast Cells: Cytological and Histotopographic Features - Dmitri Atiakshin; Vera Samoilova; Igor Buchwalow; Markus Tiemann (Cells, 2021)
The biological significance of the CD38 molecule goes beyond metabolic, enzymatic, and proliferative functions. CD38 possesses the functions of an exoenzyme and receptor, and is actively involved in the mechanisms of adhesion, migration, intercellular signaling, formation of immune synapses, and modulation of the activity of a wide range of immune and non-immune cells. The aim of this study was the immunohistochemical assessment of the cytological and histotopographic characteristics of CD38 expression in mast cells. CD38 expression was found in a minority of the mast cell population. It is characterized by wide variability from low to high levels. The intensity of CD38 expression in mast cells has organ-specific features and depends on the development of pathological processes in a specific tissue microenvironment. The mechanisms of intercellular interaction between mast cells and CD38+ cells foster new understanding of the protumorigenic or antitumor potential of tryptase.